2021
DOI: 10.3390/ijerph18030903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Respiratory Disorders on Smoking Cessation and Re-Initiation in an Italian Cohort Study

Abstract: The present study aims to prospectively assess the influence of respiratory disorders on smoking cessation and re-initiation. Three population-based Italian cohorts answered a questionnaire on respiratory health and smoking habits during 1998–2001 and after a mean follow-up (SD) of 9.1 (0.8) years. Out of 1874 current smokers and 1166 ex-smokers at baseline, 965 (51.5%) and 735 (63.0%) reported their smoking status at follow-up. From current smokers, 312 had stopped smoking at follow-up, while 86 ex-smokers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…As expected and consistent with past research( Chandola et al, 2004 , Nakajima and al'Absi, 2012 , Lynch et al, 2019 , Finocchio et al, 2021 , Saxby et al, 2022 ), alcohol drinking, and cohabitant smoking were substantial obstacles to successful cessation, and mental diseases predicted smoking relapse in women but not in men, while suffering from respiratory diseases reduced the risk of relapse. Intriguingly, we found that the negative correlation between the number of cigarettes smoked per day and relapse was most pronounced in individuals aged ≥65 years.…”
Section: Discussionsupporting
confidence: 89%
“…As expected and consistent with past research( Chandola et al, 2004 , Nakajima and al'Absi, 2012 , Lynch et al, 2019 , Finocchio et al, 2021 , Saxby et al, 2022 ), alcohol drinking, and cohabitant smoking were substantial obstacles to successful cessation, and mental diseases predicted smoking relapse in women but not in men, while suffering from respiratory diseases reduced the risk of relapse. Intriguingly, we found that the negative correlation between the number of cigarettes smoked per day and relapse was most pronounced in individuals aged ≥65 years.…”
Section: Discussionsupporting
confidence: 89%